State-of-the-art in nonlinear finite element modeling of isolated planar reinforced concrete walls. (1st September 2019) - Kolozvari, Kristijan; Biscombe, Lauren; Dashti, Farhad; Dhakal, Rajesh P.; Gogus, Aysegul; Gullu, M. Fethi; Henry, Richard S.; Massone, Leonardo M.; Orakcal, Kutay; Rojas, Fabian; Shegay, Alex; Wallace, John
Highlights: All models predict wall load capacity within ±5% for five considered specimens. All models predict nonlinear shear deformations and shear-flexure interaction. All models capture nonlinear strain distributions along the wall base and strain magnitudes within ±50%. None of the models were capable of comprehensively simulating all strength degradation mechanisms observed during the tests. Abstract: A number of finite element modeling approaches for reinforced concrete (RC) structural walls have recently become available for both research purposes and design applications. Five conceptually-different state-of-the-art finite element models for RC walls are described and evaluated in this paper, including models based on either a fixed-crack or a rotating-crack approach for simulating the biaxial behavior of concrete under plane-stress state, models characterized with either a single- or a multi-layered representation of the wall cross-section, and models with or without consideration of various individual failure mechanisms (e.g., buckling of reinforcement, out-of-plane instability). Modeling approaches were validated against experimental data obtained for five benchmark RC wall specimens, all with rectangular cross-sections, yet are differentiated by a range of salient response characteristics (e.g., aspect ratio, axial load, failure mechanism), in order to assess the capabilities of the models in representing the response of isolated planar walls under uni-directional lateral loading, as well as to identify future research directions. Results presented suggest that the models considered in this study can all capture the lateral load at yield and the peak lateral load capacity of the wall specimens with ±10% accuracy, while the initial stiffness and yield stiffness can be overestimated as much as 3.0 and 1.8 times, respectively. All models can capture nonlinear shear deformations and interaction between flexural and shear responses under cyclic loading, where the analytically-predicted flexural and shear deformations are within ±30% of the experimentally-measured values. Moderate differences between the predicted crack orientations and distributions are noted between the models, and the model results for the magnitudes of principal compressive stresses in concrete and the extent of stress localization are comparable. All models can capture the nonlinear distribution of vertical strains measured along the base of the walls, where the magnitudes of the predicted tensile and compressive strains are within ±50% of experimentally-measured strains for most models. Although some of the model formulations proved to be successful in capturing the experimentally-observed strength loss mechanisms for individual wall specimens, none of the models were capable of comprehensively simulating all of the strength degradation mechanisms observed during the tests.